Physics of pressurized hydrogen spontaneous ignition in pipes containing bends of different angles - Zhou, Xuejin; Jing, Jiaojiao; Chen, Chen; He, Le (Frontiers in Energy Research, 2024)
In the context of hydrogen-based energy storage systems, the safeguarding against spontaneous ignition during high-pressure hydrogen release is of paramount importance. This study delves into the thermal safety and management technologies pertinent to such systems by numerically investigating the effects of pipeline geometry on the risk of spontaneous ignition. Employing Large Eddy Simulation (LES) coupled with detailed chemical kinetics and a linear eddy model, the research assesses the impact of different pipe angles and burst pressures on ignition behavior. The simulations are validated against experimental data, ensuring the veracity of the findings. The results demonstrate a significant interplay between the ignition propensity and both the geometrical configuration of the pipeline and the pressure of hydrogen release. Notably, the emergence and interaction of transverse waves in pipe bends are revealed to amplify mixing processes, generating vortices that elevate the temperature and promote a conducive environment for chemical reactions leading to stable flame propagation. The ignition is shown to occur predominantly near the stoichiometric mixture ratio, suggesting a narrow ignition region. These insights are vital for enhancing the safety protocols and thermal management strategies of hydrogen-based energy storage systems, paving the way for safer and more efficient energy solutions.